Analisis Kelayakan Usaha UMKM Batik di Surabaya Kriya Galery (SKG) Siola Tunjungan - Bakhitah Zulfa; Parikesit Penangsang (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The strategically placed Surabaya Kriya Gallery (SKG) Siola Tunjungan in the city center is one batik MSME that is gaining attention. Through the use of original designs, coloring methods, and marketing strategies, SKG Siola Tunjungan has worked to develop batik with a dash of originality and creativity. Nonetheless, a thorough feasibility study must be carried out to guarantee the company's survival and expansion. The purpose of this study is to evaluate the SKG Siola Tunjungan Batik UMKM company's viability in Surabaya. Qualitative descriptive research is part of this study design. Interviews, documentation, and questionnaires are the methods used in this study to collect data. Based on financial analysis using the feasibility Benefit Cost Ratio (B/C) which divides income by total costs. The highest value obtained was 0,89 and the lowest was 0,38, so the Batik UMKM business run by batik entrepreneurs in Surabaya Kriya Gallery (SKG) Siola Tunjungan was considered suitable to operate. Financial aspects are analyzed using Revenue Cost Ratio (R/C) feasibility analysis which divides income by total costs. The highest value obtained was 1,89, while the lowest was 1,38. The financial aspect was also analyzed using Return On Investment (ROI) feasibility analysis, namely dividing the income by investment costs multiplied by 100. The highest value obtained was 0,85%, while the lowest was 0,66%.